Populações de plantas e estratégias de irrigação na cultura da soja. - Kuss, Rejane Cristina Roppa (2006)
The cultivation of the soybean in the Rio Grande do Sul is done under varied environmental terms and predominantly without irrigation. However, soybean has been used as an alternative tillage to tillage rotation in the irrigated agriculture, being sown mostly in late cultive. However when sown lately, grain yield soybean is low by exposed at biotic factors and abiotics that can be limiting to cultive productivity. The objective of these experiments were to verify which effect of irrigation and plant population more adequate to tillage condition of soybean sown after time recommends in Santa Maria. The experiment was conducted during January and May 2005 at Experimental Area from Agricultural School of Santa Maria, UFSM. The sowing was in 10 of January 2005. It was used conventional cultivate of soybean Coodetec 205 (CD 205) launched in 1998 by Ocepar/Coodetec. The experiment was a bifactorial, having as levels three handlings of irrigation and two plant population, totalizing six treatments with four repetitions, resulting in 24 experimental units. The experiment design was randomized blocks with subdivided bits. In the main bits were distributed three irrigation handlings: 1) no irrigated; 2) irrigated all cycle; and 3) irrigated in critical periods. In subplot were distributed both plants populations (250.000 and 400.000 plants.ha-1). Harvest of the plants was accomplished in 21st 2005, at 125 days after emergency. So much the handling of the irrigation to soybean tillage, regarding adaptation of the plants population caused differences in grain yield soybean sown after time recommends. The biggest grain yield was obtained with irrigation during all cycle of the soybean in the population of 400.000 plants.ha-1, that don`t differ of irrigated plants all cycle in the population of 250.000 plants.ha-1. The grain yield of no irrigated plants had an increment of 21,5% with the increase of plant population to 400.000 plants.ha-1. For irrigated plants all cycle and only irrigated in critical periods, the grain yield don`t show significant differences between plant populations. Despite of pods number for plant have been larger for the populations minors, pods number for square meter was larger for the population of 400.000 plants.ha-1 irrigated all cycle compensated by the largest number of plants. The number of grains for pod was not influenced by irrigation, neither by the plant populations. The middle weight of grains was larger to population 400.000 plants.ha-1 and to not irrigated plants.